Herbert List ou « la mise en présence de l’absence » - Kolar, Adriana (CV Photo, 2002)
The retrospective exhibition Herbert List – Flâneur romantique raises questions that come less from the photographs than from the proposed discourse. List's career and life are presented as exemplars without the slightest trace of a shadow. It is mentioned that his way of life, his homosexual friendships, and his partly Jewish upbringing made him suspect to the Nazi regime, but nothing is said about the war period and his enlistment in the Wehrmacht as chief of the mapping department in 1944-45. Such a presentation is stunning as an accounting of an artist whose work is in fact distinguished by his "plays of shadow and light."